Waste Management Strategy Through Community Participation In Realizing Good Governance In Kupang City - Maria Elerina Douk Tunti; Anthon S. Y. Kerihi; Karmila D.L.Mutia (Green Publisher Indonesia, 2021)
This study aims to formulate a strategy for waste management through community participation in realizing good governance in Kupang City. This type of research is quantitative descriptive using a questionnaire with SWOT analysis. Respondents are residents of Kupang City. The results found that the increase in the population of the city of Kupang has an impact on increasing waste production. Even though waste production continues to increase, as the central government of NTT, stakeholders are trying to improve waste management and make Kupang a healthy, friendly and clean city. The strategies used are 1) synchronizing waste management programs and budgets between the City Government and stakeholders, 2) expanding the collaboration between the City Government and Universities in designing effective and efficient waste management technology, 3) advocating to build public awareness of waste management, 4) exploring opportunities for collaboration between The municipal government with third parties who are concerned with waste management including the preparation of waste processing volunteers, 5) soft skill trainings on waste management and joint budget waste management, 6) build and facilitate coordination with stakeholders and regular communication to the community through Kelurahan and RT/ RW, 7) budget allocation in the APBD to recruit field workers who are committed to managing waste, and the City Government budget allocation for spending on the procurement of public area trash cans that separate organic and non-organic waste.